The correspondence - Whitman, Walt, 1819-1892.; Genoways, Ted. (Iowa City : University of Iowa Press, 2004)
Among the more than one hundred fifty letters collected in this volume are numerous correspondences concerning Whitman's Civil War years, including a letter sending John Hay, the personal secretary to Abraham Lincoln, a manuscript copy of "O Captain, My Captain!" Additional letters address various aspects of the production of Leaves of Grass, the most notable being an extensive correspondence surrounding the Deathbed Edition, gathered by Whitman's friend Horace Traubel, and reproduced here for the first time. Most significantly, this volume at last incorporates Whitman's early letters to Abrah.
Foreword; Introduction; A List of Whitman's Correspondents; Abbreviations; The Correspondence; Calendar of Letters to Whitman (Revised 2003); Index to Volume VII
Supplements the six volumes of The correspondence in The collected writings of Walt Whitman, published by New York University Press 1961-1977.
"Volume VII."
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: Whitman, Walt, -- 1819-1892 -- Correspondence; Whitman, Walt, -- 1819-1892; Poets, American -- 19th century -- Correspondence; Poètes américains -- 19e siècle -- Correspondance; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; LITERARY CRITICISM -- Poetry; Poets, American; 1800-1899; Personal correspondence